Production of bergenin, an active chemical constituent in the callus of Bergenia ciliata (Haw.) Sternb. - Shrestha, Umesh Krishna; Pant, Bijaya (Botanica Orientalis: Journal of Plant Science, 2012)
In vitro culture of Bergenia ciliata (Haw.) Sternb. was carried out for the examination of bergenin content. Leaf explants were cultured in MS (Murashige and Skoog) basal media supplemented with or without phytohormones. The hormonal series maintained were in the range of 0-2 mg l-1 for BAP (6-benzyl amino purine) and 0-1.5 mg l-1 for NAA (α-naphthalene acetic acid). Bergenin content of in vitro grown tissues of B. ciliata was compared with that of wild plants collected from three different localities of Nepal. The best growth of callus and plantlets occurred in the media containing BAP 1.0 mg l-1 + NAA 1.0 mg l-1 and BAP 1.5 mg l-1 + NAA 1.0 mg l-1. Production of bergenin was high in the media supplemented with 1.0 mg l-1 BAP + 1.5 mg l-1 NAA (3.40 μg g-1) and 2.0 mg l-1 BAP + 1.5 mg l-1 NAA (3.05 μg g-1) under experimental condition. The bergenin content in the wild plants collected from Langtang, Jumla and Godawari was found to be 4.28 μg g-1, 4.53 μg g-1 and 3.64 μg g-1 respectively. This study shows that the in vitro cultured callus of B. ciliata is capable of synthesizing bergenin in quantity comparable to that of the wild plant. doi: http://dx.doi.org/10.3126/botor.v8i0.5557 Botanica Orientalis – Journal of Plant Science (2011) 8: 40-44